2009
DOI: 10.1007/s11262-009-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

Haemagglutinin and neuraminidase characterization of low pathogenic H5 and H7 avian influenza viruses isolated from Northern pintails (Anas acuta) in Japan, with special reference to genomic and biogeographical aspects

Abstract: Pintails constitute an important host of avian influenza viruses (AIVs). Genetic, molecular, and antigenic characteristics of H5 and H7 AIVs, which we isolated from northern pintails (Anas acuta) wintering in Japan, were analyzed and found to be linked to various ecological features, chiefly in terms of gene geography, as shaped by various migratory aquatic host species. Although all the isolates were found to be of low pathogenicity (LP), we explored gene predispositions that may potentially underlie tentativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Interestingly, Jahangir et al (2009) found a high isolation rate of AIV H7N7 in northern pintails (Anas acuta) in wintering season 2007/ 08 in Japan, and similarly to our studies, on one occasion the virus was detected twice at one site, 2 months apart. A phylogenetic study of H7 and N7 genes revealed that these isolates were very similar or virtually identical (Jahangir et al, 2010).However, the high frequency of H7N7 isolation in that region was noted exclusively in one wintering season as opposed to our study in which we demonstrated the presence of AIV with genetically related genes between two consecutive winter seasons in the same area.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, Jahangir et al (2009) found a high isolation rate of AIV H7N7 in northern pintails (Anas acuta) in wintering season 2007/ 08 in Japan, and similarly to our studies, on one occasion the virus was detected twice at one site, 2 months apart. A phylogenetic study of H7 and N7 genes revealed that these isolates were very similar or virtually identical (Jahangir et al, 2010).However, the high frequency of H7N7 isolation in that region was noted exclusively in one wintering season as opposed to our study in which we demonstrated the presence of AIV with genetically related genes between two consecutive winter seasons in the same area.…”
Section: Discussioncontrasting
confidence: 92%
“…Despite the great importance, there are few reports describing phylogenetic analysis of H7N7 strains isolated from their natural reservoir (Campitelli et al, 2008;Jahangir et al, 2010;Metreveli et al, 2010). Furthermore, there is still little information dealing with virushost ecology.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we analyzed the NS genes of H5 and H7 subtypes, in addition to the above-mentioned AIVs. Moreover, polymerase acid (PA), nucleoprotein (NP), M, and NS genes of H5N9 strain, an uncommon antigenic combination which we isolate for the first time in Asia [19], were further looked into in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of AIVs is possible between migrating birds and domestic poultry through synanthropic avian species or direct contact with birds in poultry farms [11]. Some countries have decided to use vaccination as the strategy to stop the disease from spreading [3,14,22,24,28,33].…”
mentioning
confidence: 99%
“…Madin-Darby canine kidney (MDCK) cells were employed for culturing of low-pathogenic AIV (LPAIV) H7N1 (A/duck/Aomori/395/04) [11]. The cells were cultured in Eagle's minimum essential medium (EMEM; Nissui Pharmaceutical Co., Ltd., Tokyo, Japan), supplemented with 0.3 % of tryptose phosphate broth, 5 % fetal of bovine serum (FBS), L-glutamine (0.3 mg/mL), NaHCO 3 (1.4 mg/mL), and antibiotic-fungicide cocktail (penicillin [100 IU/mL], streptomycin [0.1 mg/mL] and amphotericin B [0.5 lg/mL]).…”
mentioning
confidence: 99%